2016
DOI: 10.1038/nphys3665
|View full text |Cite
|
Sign up to set email alerts
|

Realization of a tunable artificial atom at a supercritically charged vacancy in graphene

Abstract: Graphene's remarkable electronic properties have fuelled the vision of a graphene-based platform for lighter, faster and smarter electronics and computing applications. One of the challenges is to devise ways to tailor graphene's electronic properties and to control its charge carriers [1][2][3][4][5] . Here we show that a single-atom vacancy in graphene can stably host a local charge and that this charge can be gradually built up by applying voltage pulses with the tip of a scanning tunnelling microscope. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
165
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(178 citation statements)
references
References 32 publications
13
165
0
Order By: Relevance
“…Recent studies have shown that these defects can indeed give rise to localized resonant states that are pinned in energy close to the Dirac point 32,[54][55][56] . When a negative back gate is applied these localized states reside well above the Fermi energy and therefore cannot trap the hot carriers that have characteristic energies only slightly above .…”
Section: S15 Scanning Gate Thermometry Of Hbn/graphene/hbn Devicementioning
confidence: 99%
“…Recent studies have shown that these defects can indeed give rise to localized resonant states that are pinned in energy close to the Dirac point 32,[54][55][56] . When a negative back gate is applied these localized states reside well above the Fermi energy and therefore cannot trap the hot carriers that have characteristic energies only slightly above .…”
Section: S15 Scanning Gate Thermometry Of Hbn/graphene/hbn Devicementioning
confidence: 99%
“…Graphene on hBN samples are fabricated using the poly(methyl methacrylate) (PMMA)-based dry transfer method (44). hBN is exfoliated on a 300-nm SiO 2 /Si substrate.…”
Section: Methodsmentioning
confidence: 99%
“…Each transformed C atom gives rise to a vacancy in the π band, producing a quasibound state localized near the defect. The energy of such a localized state depends on the adatom type, taking values LS ∼ 10−100 meV, i.e., positioned in the direct vicinity of the Dirac point [24][25][26]. In transport, such defects act as resonant scatterers, with the scattering cross section exhibiting a sharp resonance at = LS .…”
Section: Model Of Electronic Coolingmentioning
confidence: 99%
“…Ab initio and STM studies [24][25][26] have shown that quasibound states with energies near the Dirac point arise in a robust manner when adatoms or polar groups such as H, F, CH 3 , or OH bind covalently to carbon atoms, transforming the trigonal sp 2 orbital to the tetrahedral sp 3 orbital. Each transformed C atom gives rise to a vacancy in the π band, producing a quasibound state localized near the defect.…”
Section: Model Of Electronic Coolingmentioning
confidence: 99%